Revelation Of Jesus Christ: Commentary on the Book of Revelation. - Cardoso, Matheus (Kerygma, 2010)
STEFANOVIC, Ranko. Revelation Of Jesus Christ: Commentary on the Book of Revelation. Berrien Springs, EUA: Andrews University Press, 2002.